2013
DOI: 10.1063/1.4798636
|View full text |Cite
|
Sign up to set email alerts
|

Surface-termination-dependent Pd bonding and aggregation of nanoparticles on LaFeO3 (001)

Abstract: The bonding and morphology of Pd clusters deposited on the LaO- and FeO2-terminated LaFeO3 (001) surface were studied using periodic density functional methods together with scanning transmission electron microscopy. We show that Pd tends to aggregate to three-dimensional (3D) clusters on both terminations since the Pd-Pd cohesive energy is larger than the Pd-LaFeO3 adhesive energy. However, from the kinetic point of view, Pd migration on the LaO termination is facile, while stronger interactions between Pd an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…First of all, we attempt to investigate the binding of Pt atom on the two commonly observed CaO-and TiO 2 -terminated surfaces. Similar to the previously studied Pd-doped LaFeO 3 system, 29,30 the one-fold O I site at the CaO-terminated surface and the four-fold O H site at TiO 2 -terminated surface are found to be the most favorable binding positions for Pt (see Fig. 1).…”
Section: Introductionsupporting
confidence: 80%
“…First of all, we attempt to investigate the binding of Pt atom on the two commonly observed CaO-and TiO 2 -terminated surfaces. Similar to the previously studied Pd-doped LaFeO 3 system, 29,30 the one-fold O I site at the CaO-terminated surface and the four-fold O H site at TiO 2 -terminated surface are found to be the most favorable binding positions for Pt (see Fig. 1).…”
Section: Introductionsupporting
confidence: 80%
“…If it is surmised that some Pd moves from Pd-doped LFO onto the surface upon aging, thus accounting for the increase in integral CO conversion, then conversely, some of the Pd deposited onto the surface of Pd-impregnated LFO likely reacts and migrates into the perovskite matrix. Both processes are expected, according to the original literature on self-regenerating catalyst materials [8], and both have been observed, to relatively limited degrees, in the model planar catalyst [15,19]. Thus, both initial states (Pd-impregnated and Pd-doped LFO) are expected to evolve toward a common one, consisting of a mixture of metallic Pd particles and isolated Pd cations on the surface of LFO.…”
Section: Discussionmentioning
confidence: 85%
“…A surface termination change might partially explain this result. Calculations have shown that for LaFeO 3 (0 0 1) the LaO termination is thermodynamically favored versus the FeO 2 termination under UHV conditions at 727 • C [12]. XPS analysis has also shown a temperature-dependent switch in the termination of LaAlO 3 [33], which was believed to stem from oxygen deficiencies in the first atomic layer.…”
Section: Resultsmentioning
confidence: 95%
“…Calculations have shown that oxygen reduction occurs preferentially on the FeO 2 -terminated LFO (0 1 0) surface rather than the LaO-type termination [11]. In addition, simulations suggest that the termination on LFO (0 0 1) can significantly affect Pd migration into the perovskite lattice, which can impact "intelligent catalysts" automotive exhaust catalysis [12]. Aside from the surface termination, atomic vacancies are also predicted to influence the chemistry of LFO catalysts.…”
Section: Introductionmentioning
confidence: 97%